Electrochemical behavior of thick rust layers on steel artefact: Mechanism of corrosion inhibition. (1st September 2019) - Rocca, Emmanuel; Faiz, Hadri; Dillmann, Philippe; Neff, Delphine; Mirambet, François
Abstract: The electrochemical behavior of aged corrosion layers (CL) on artefact was studied, in corrosive reference water without and with non-toxic corrosion inhibitors such as decanoate ions and flavonoids compounds, constituting the condensed tannins, such as catechin. Electrochemical impedance spectroscopy measurements on the metal/CL system and voltammetric studies of FeOOH phases on carbon paste electrode show that the corrosion inhibition mechanism is mainly based on the blocking of the dissolution of FeOOH-type phase and the decrease of the diffusion of ionic species in the pores network of CL. Indeed, the formation of iron decanoate, revealed by X-ray diffraction and microscopic observation, inhibits the electrochemical activity of FeOOH-type phases and blocks the electrochemical dissolution of FeOOH into Fe 2+ cations. On the other hand, the catechin compound modifies the surface of rust compounds into a blue-black compound, but this modification has a poor influence on the electrochemical activity of FeOOH-type compounds.